Trueperella pyogenes multispecies infections in domestic animals: a retrospective study of 144 cases (2002 to 2012) - Ribeiro, M. G. [UNESP]; Risseti, R. M. [UNESP]; Bolanos, C. A. D.; Caffaro, K. A.; Morais, A. C. B. de; Lara, G. H. B. [UNESP]; Zamprogna, T. O. [UNESP]; Paes, A. C. [UNESP]; Listoni, F. J. P. [UNESP]; Franco, M. M. J. (Taylor &francis Ltd, 2015)
Background: Formerly, Arcanobacterium pyogenes was recently renamed Trueperella pyogenes. This opportunistic bacterium is related to miscellaneous pyogenic infections in animals. Most studies involving T. pyogenes are case reports, whereas few surveys have focused the major aspects of T. pyogenes infections involving a case series study design.Objective: The aim of this study was to retrospectively evaluate selected epidemiological and clinical aspects, as well as the in vitro antimicrobial susceptibility pattern of 144 cases of T. pyogenes infections among domestic animals from 2002 to 2012.Animals and methods: T. pyogenes was isolated from different clinical specimens from cattle, goats, sheep, pigs, horses, dogs, and buffaloes. Correlations were assessed by the Chi-square or Fisher's exact tests.Results: Mastitis (45.1%), abscesses (18.0%), pneumonia (11.1%), and lymphadenitis (9.0%) were the most common clinical manifestations. In addition, the organism was also isolated from other miscellaneous clinical specimens from cases of septicemia, encephalitis, pyometra, prostatitis, orchitis, seminal vesiculitis, pericarditis, and omphalitis. No statistical association was observed between T. pyogenes infections and age, gender, or season across the study. The most effective drugs against the pathogen were florfenicol (99.1%), cefoperazone (96.0%), cephalexin (95.0%), and ceftiofur (94.8%). High resistance rates were observed against trimethoprim-sulfamethoxazole (49.3%), followed by norfloxacin (10.9%) and tetracycline (9.2%).Conclusions: This study highlights the diversity of clinical manifestations and the opportunistic behavior of T. pyogenes infections in domestic animals, with predominance of mastitis, abscesses, pneumonia, and lymphadenitis. It also reinforces the importance of knowing the susceptibility profile before initiating therapy, to improve antimicrobial therapy approaches.
Keywords: Horse; Livestock; Cattle; Arcanobacterium pyogenes; Trueperella pyogenes; Goat; Antimicrobial susceptibility pattern; Overview; Buffalo; Pig; Sheep; Brazil; Dog